ANALISIS MYLOFT DALAM MEMENUHI KEBUTUHAN INFORMASI PEMUSTAKA UPI - Rahmawati, Eka; Arya, Ghaitsa Zahira; Khusnul H, Resya Fauka; Dewi, Laksmi; Setiawati, Linda (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2022)
The Covid-19 pandemic has forced every activity to adapt to new habits, including the library. To overcome this, the UPI Library provides online services in the form of e-resources that can be accessed using the MyLOFT application. This study aims to determine how librarian services, service quality, and the role of e-resources services at MyLOFT are in terms of ease of access and in meeting the information needs of users. This research method uses a descriptive quantitative method. The sample of this study was active UPI students aged 18-22 years. The results showed that socialization and guidelines helped users in facilitating access to e-resources on MyLOFT, the quality of the service also had a pretty good appearance that made it easier for users to access, this service has also played quite a role in meeting the information needs of users at UPI. Although it is sufficient to meet the information needs of users, this service must continue to improve its services and continue to strive to provide the best service, so that the e-resources service on MyLOFT can be increasingly recognized and able to meet the information needs of users.